2020
DOI: 10.1159/000511725
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperfusion with CytoSorb as Adjuvant Therapy in Critically Ill Patients with SARS-CoV2 Pneumonia

Abstract: We report a preliminary experience of adjuvant therapy with Hemoperfusion (HP) in patients with Severe Acute Respiratory Syndrome-CoronaVirus 2 (SARS-CoV2) pneumonia. Currently, there are no approved treatments for CoronaVirus Disease 19 (COVID-19); however, therapeutic strategies based on the preclinical evidence include supportive measures, such as oxygen supplementation, antiviral, and anticoagulant agents. Despite these treatments, 10% of patients worsen and develop severe acute respiratory distress syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 10 publications
3
76
1
1
Order By: Relevance
“…Unlike the previous study by Rampino et al 29 , in which the mean PaO2/FiO2 ratio was higher and patients did not require invasive mechanical ventilation, all our patients presented a considerable deleterious clinical situation, with a mean PaO2/FIO2 ratio of 103 (18.4), and 2 of them needed ECMO support. The hemoadsorption delivering strategy in our study was different from Rampino´s study.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Unlike the previous study by Rampino et al 29 , in which the mean PaO2/FiO2 ratio was higher and patients did not require invasive mechanical ventilation, all our patients presented a considerable deleterious clinical situation, with a mean PaO2/FIO2 ratio of 103 (18.4), and 2 of them needed ECMO support. The hemoadsorption delivering strategy in our study was different from Rampino´s study.…”
Section: Discussioncontrasting
confidence: 90%
“…Despite these recommendations, clinical experience is scarce and comes mainly from case reports 26 27 28 and some case series. Rampino et al 29 .reported a case series of 9 consecutive critically ill patients with SARS-CoV-2 and respiratory failure requiring continuous positive airway pressure. There were no patients meeting the clinical criteria for invasive mechanical ventilation at the hemoadsorption initiation.…”
Section: Discussionmentioning
confidence: 99%
“…This is a case of uncontrolled inflammation, which is related to disease severity and unfavorable outcomes [ 4 ]. These findings provided a rational basis for using anti-inflammatory drugs and extracorporeal procedures with a high capacity of cytokine adsorption and removal in the treatment of COVID-19 [ 5 , 6 ]. Clinically, COVID-19 may involve patients of all ages, but it appears particularly severe in old subjects with pre-existent health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Another observational study from Italy reported on nine consecutive COVID-19 patients with severe pneumonia requiring continuous positive airway pressure [56]. Five of the patients were treated with hemoperfusion using a CytoSorb adsorber, while the remaining four patients were not treated with CytoSorb and served as the control group.…”
Section: Clinical Datamentioning
confidence: 99%
“…Based on the available published data, it seems that the most frequent indications for CytoSorb treatment in these critically ill COVID-19 patients were hemodynamic instability, need for renal replacement therapy [26,[31][32][33], and severe ARDS requiring ECMO [55,65]. Apart from one study in which treatment was started at an earlier stage when patients did not need vasopressors or mechanical ventilation [56], most patients were very sick on study entry.…”
Section: Target Patient Populationmentioning
confidence: 99%